1997
DOI: 10.1111/j.1600-0722.1997.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cephalometric classification methods for sagittal jaw relationships

Abstract: The present study evaluated how 2 widely used cephalometric sagittal analyses, ANB angle and WITS appraisal, classify skeletal classes I, II, and III in a random selection of 497 Finnish boys aged 4-20 years. This distribution was also compared with the visual inspection of cephalometric structures judged by 2 university instructors in orthodontics. The results showed remarkable differences and even sparked controversy concerning classification of the sagittal jaw relationships. The ANB angle and the WITS appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
3
12
1
5
Order By: Relevance
“…Our results revealed a statistically significant regression between ANB angle and Wits appraisal which was in agreement with Hurmerinta et al and Zhou et al, however, Hurmerinta et al reported a lower R2 value [10,29]. This might be due to age differences because their study included patients with primary dentition [29].…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed a statistically significant regression between ANB angle and Wits appraisal which was in agreement with Hurmerinta et al and Zhou et al, however, Hurmerinta et al reported a lower R2 value [10,29]. This might be due to age differences because their study included patients with primary dentition [29].…”
Section: Discussionsupporting
confidence: 92%
“…Each or patient's sagittal skeletal relationship was classified into skeletal classes I, II III according to the ANB (point A, nasion, point B) angle on lateral cephalograms obtained for pre‐treatment diagnosis and treatment planning as follows: skeletal Class I, 0°−4°; skeletal Class II, >4°; skeletal Class III, <0° .…”
Section: Methodsmentioning
confidence: 99%
“…Each or patient's sagittal skeletal relationship was classified into skeletal classes I, II III according to the ANB (point A, nasion, point B) angle on lateral cephalograms obtained for pre-treatment diagnosis and treatment planning as follows: skeletal Class I, 0°À4°; skeletal Class II, >4°; skeletal Class III, <0° ( 19). We also assessed patients using the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN-DHC), which represents a simple, easy and reasonably reproducible method of determining (20).…”
Section: Data Collection and Instrumentsmentioning
confidence: 99%
“…A pesar de que el ángulo ANB es ampliamente utilizado en odontología, habitualmente se usa considerando un valor promedio de 2º y una variación de la normalidad de más/menos 2º (37) . Dicho abordaje diagnóstico no toma en cuenta la edad ni los fenómenos de crecimiento y desarrollo esperados para un determinado individuo, que se reflejan en la reducción del ángulo ANB a lo largo del desarrollo (24,26,29,31,38,39) . Esto puede llevar a un diagnóstico errado, y por ende a resultados clínicos distintos de los esperados.…”
Section: Discussionunclassified
“…Esto ha sido reportado por numerosos autores (24)(25)(26)(27)(28)(29)(30) . Utilizando una muestra longitudinal, Ochoa y Nanda (30) evaluaron 28 individuos de ambos sexos y observaron que el ángulo ANB disminuye significativamente durante el crecimiento.…”
Section: Revisiónunclassified